The philosophical essence of innovation activity - Azizbek Egamberdiev (Universitas Muhammadiyah Sidoarjo, 2019)
The article highlights the role of innovative thinking in organizing research activities. Philosophical analysis of organizational, social, financial and economic aspects of the organization of innovative activity. Priorities of innovation activity in Uzbekistan and main trends in it were revealed. In addition, a number of proposals and recommendations on innovative activities have been developed